(untitled) (La Aljaba. Segunda Época. Revista de Estudios de la Mujer, 2017)
The article focuses in the study of two kinds of female works: first, a dependency job, female street sweepers at Neuquén city; secondly, saleswomen who operate their pretended leisure in an informal work ratio disguised in autonomy labor. Our approach obviates an economic reductionism and places work female world in power relationships and gender inequality social constructions. Futhermore, we claim that gender inequalities are supported by social ideologies which state what female/male have to be.